Hydrogen Sulfide Ameliorates Angiotensin II-Induced Atrial Fibrosis Progression to Atrial Fibrillation Through Inhibition of the Warburg Effect and Endoplasmic Reticulum Stress - Hu, Heng-Jing; Wang, Xiu-Heng; Liu, Yao; Zhang, Tian-Qing; Chen, Zheng-Rong; Zhang, Chi; Tang, Zhi-Han; Qu, Shun-Lin; Tang, Hui-Fang; Jiang, Zhi-Sheng (Frontiers in Pharmacology, 2021)
Atrial fibrosis is the basis for the occurrence and development of atrial fibrillation (AF) and is closely related to the Warburg effect, endoplasmic reticulum stress (ERS) and mitochondrion dysfunctions-induced cardiomyocyte apoptosis. Hydrogen sulfide (H2S) is a gaseous signalling molecule with cardioprotective, anti-myocardial fibrosis and improved energy metabolism effects. Nevertheless, the specific mechanism by which H2S improves the progression of atrial fibrosis to AF remains unclear. A case-control study of patients with and without AF was designed to assess changes in H2S, the Warburg effect, and ERS in AF. The results showed that AF can significantly reduce cystathionine-γ-lyase (CSE) and 3-mercaptopyruvate thiotransferase (3-MST) expression and the H2S level, induce cystathionine-β-synthase (CBS) expression; increase the Warburg effect, ERS and atrial fibrosis; and promote left atrial dysfunction. In addition, AngII-treated SD rats had an increased Warburg effect and ERS levels and enhanced atrial fibrosis progression to AF compared to wild-type SD rats, and these conditions were reversed by sodium hydrosulfide (NaHS), dichloroacetic acid (DCA) or 4-phenylbutyric acid (4-PBA) supplementation. Finally, low CSE levels in AngII-induced HL-1 cells were concentration- and time-dependent and associated with mitochondrial dysfunction, apoptosis, the Warburg effect and ERS, and these effects were reversed by NaHS, DCA or 4-PBA supplementation. Our research indicates that H2S can regulate the AngII-induced Warburg effect and ERS and might be a potential therapeutic drug to inhibit atrial fibrosis progression to AF.